Estudo do comportamento tribológico de compósitos a base de poliéster insaturado - Sakuma, Valquiria Yurie (2019)
Polymeric composites are materials capable to combine mechanical and tribological features, which are not found in traditional engineering materials. The present work intends to discuss the tribological behavior of composites with polyester matrix reinforced by two kinds of particulate materials (graphite and PEEK). The methodology for the composites confection was developed and composites with 3, 6 and 12% of graphite and PEEK were manufactured. With the produced material, tribological tests were performed to evaluate the influence of presence and the amount of addition material in polyester tribological features. This composites tribological behaviors were analyzed through the application of tests as scratch, drying, with Rockwell C penetrators. The friction behavior was evaluated as a function of the normal load applied, speed and the material type. Surface analysis were performed through techniques of white light interferometry, scanning electron microscopy and FTIR. From tribological test results, it was able to evaluate the composite tribological behavior and the acting wearing mechanism. It was observed that the main wearing mechanisms were plastic deformation and micro scratches abrasion. A very little amount of wear particles was also observed, but there was no formation of protective tribofilm. For all the materials, the steady state period was reached near 2 mm and the friction rate showed more oscillation for PEEK composites, influenced by material particles. The load presented more influence, both in the friction value and the wear mechanisms. In general, it can be concluded that composites with 3% of particle show better friction results. And that the variation of the tests parameters had little influence on the type of wear micromechanism.